A Study of Achievement Motivation in Relation to Anxiety, Depression, and Stress among Adolescents During Covid 19 Pandemic in Kerala - Shiny P. K.; Dr. Soumya Startlet C. T. (International Journal of Indian Psychȯlogy, 2022)
Achievement motivation is the driving force of life. This motivation helps each individual to attain his or her goals in life. In this study an attempt was made to study the achievement motivation among adolescents during covid 19 pandemic and found any relation with other variables like anxiety, depression and stress. During the outbreak of covid 19 pandemic each individual went through uncertainly situations. All these conditions not only affect the adolescence and their family members but also the entire world. For this purpose, a sample of 133 adolescents was selected from Kerala state.  Achievement motivation scale by Prof. Pratibha Deo and Dr. Asha Mohan and anxiety depression, stress (ADSS-BSPSA) scale by Prof. Pallavi Bhatnagar and her colleagues were used. Mean, standard deviation, t-test, ANOVA and Carl Pearson correlation were applied to analyse the data. The major finding was adolescents’ achievement motivation found to be greatly reduced during the covid 19 pandemic and there was no significant gender difference in achievement motivation, anxiety, depression and stress of adolescent. There was a positive relation between achievement motivation and anxiety.